Essere “prima Campoformio”. Ipotesi indiziarie su Roversi e Fortini - Fichera, Gabriele (L'ospite ingrato, 2024)
This study intends to explore some aspects of the relationship between Roversi and Fortini, identifying Dopo Campoformio as the work on which it is possible to establish a dialogue between the two writers. The comparison starts from an ethical-ideological premise: the problem of the delay with which men often face the decisive historical events that concern them, and therefore the idea expressed by a verse of Rebora according to which «to live is to justify oneself» («vivere è giustificarsi »). In a second moment the analysis, now focused on the concreteness of the texts, is aimed at verifying the existence of an extensive common lexical area, of a Reborian nature, which links the two poetic experiences, despite the ineliminable dialectic of being before and of being “after Campoformio”.